Sosialisasi Waktu Penguraian Sampah dan Dampaknya terhadap Kesehatan: Membangun Kesadaran Lingkungan Masyarakat Desa Kubang Utara Sikabu - Nazillaturrahmi; Sandra Dewi; Hasby Assidiqi; Fresia Grestiana; Fitra Gunarti (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community service activity was motivated by the low awareness and understanding of residents in Kubang Utara Sikabu Village regarding waste decomposition time and its impact on health and environmental sustainability. The village was selected due to the high generation of household waste, the absence of an effective waste sorting system, and the prevailing practice of burning or burying waste indiscriminately. The main objective of this activity was to educate the community about the differences in decomposition times between organic and inorganic waste, as well as to raise awareness of health risks caused by improper waste management. This study employed a qualitative approach through in-depth interviews with two key informants, Mrs. Nelly and Mrs. Sofia. The results showed significant improvement in knowledge and behavioral changes, including household waste segregation, composting of organic waste, and planning for separate waste collection facilities in each neighborhood. Community-based environmental education proved effective in fostering ecological awareness, strengthening healthy living behaviors, and supporting the creation of a cleaner and more sustainable environment.